Producing Fertiliser for Bok Choy Using Waste From Silica Water Filter - Anuar, Muhammad Aidiel; Ahmad, Sufizar (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Water filter was created to make sure the people on this Earth are able to consume or use clean and fresh water, but once the water filter is not usable anymore, it is thrown away. Therefore, this research aims to reuse the water filter for other purposes. In this research, the waste was used for agriculture, repurposing it to enhance plant quality and growth. A silica water filter was taken and fabricated, processed to be combined with the current fertiliser to help the growth of the studied plant. The silica water was crushed and sieved until it reached 40 microns, and then mixed with fertiliser at 5%, 10% and 15%. It shows specimens with fertiliser mixed with silica had better height and more leaves count if compared to the specimens with no silica added.